Temperature-dependent ferroelastic behaviour of antiferroelectric AgNbO3 - Shi, Xi; Eckstein, Udo; Lang, Sabrina; Cicconi, Maria Rita; Khansur, Neamul Hayet (Acta Materialia, 2022)
The macroscopic ferroelastic response of polycrystalline AgNbO3 was investigated under the uniaxial com-pressive stress of up to-300 MPa from-150 degrees C to 450 degrees C, covering weak ferroelectric, antiferroelectric, and paraelectric phase regions. It is found that AgNbO3 exhibits ferroelasticity in the weak ferroelectric (M- 1 ), antiferroelectric (M- 2 , M- 3 ), as well as the paraelectric regions (O and T), i.e. displaying ferroelas-tic hysteresis and remnant strain. The changes in mechanical parameters such as coercive stress, back switching strain, and remnant strain values reflect the specific crystal symmetry features at different phase regions together with the influence of temperature on domain wall motion. With stress removed and cooled down to room temperature, X-ray diffraction showed that the sample (at M (1) state) exhibited different degrees of remnant domain textures and lattice strains, depending on its phase state when being compressed. Additionally, in situ stress-and temperature-dependent Raman spectroscopy measurements revealed that uniaxial compressive stress could induce changes in NbO6 octahedra and cation displace-ment, especially for high-temperature phases. Overall, the ferroelasticity, effects of stress on the structure and phase transitions offer opportunities for property engineering of AgNbO3 in capacitor applications. (C)& nbsp;2022 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
CRIS-Team WoS Importer:2022-06-03